2021
DOI: 10.1186/s40001-021-00591-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of critically ill mechanically ventilated COVID-19 patients receiving interleukin-6 receptor antagonists and corticosteroid therapy: a preliminary report from a multinational registry

Abstract: Background Interleukin-6 receptor antagonists (IL-6RAs) and steroids are emerging immunomodulatory therapies for severe and critical coronavirus disease (COVID-19). In this preliminary report, we aim to describe the epidemiology, clinical characteristics, and outcomes of adult critically ill COVID-19 patients, requiring invasive mechanical ventilation (iMV), and receiving IL-6RA and steroids therapy over the last 11 months. Materials and methods In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The 148 included studies were published between December, 2019, and May, 2021. 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , ...…”
Section: Resultsmentioning
confidence: 99%
“…The 148 included studies were published between December, 2019, and May, 2021. 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Most of the previous large national studies have shown that the median age of the affected population was between 35 and 45 years, and males were affected more than females [ 13 , 14 ]. Certain studies have addressed special populations, such as the elderly, or those with severe disease, such as patients on mechanical ventilation, or as part of the RCT of an interventional study [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, 45 (5.3%) patients received corticosteroids, as shown in a study on the clinical characteristics and outcomes of critically ill mechanically ventilated patients with COVID-19 who received interleukin-6 receptor antagonist (IL-6RA) and corticosteroid therapy. [ 29 ] On day 28, compared with steroid use alone, IL-6RA use was associated with an adjusted incidence rate ratio (aIRR) of 1.12 (95% confidence interval [CI], 0.88, 1.4) for ventilator-free days, while combination therapy was associated with an aIRR of 0.83 (95% CI, 0.6–1.14). The use of IL-6RA was associated with an adjusted odds ratio (aOR) of 0.68 (95% CI, 0.44–1.07) for the 28-day mortality rate, while a combination therapy of IL-6RA and steroids was associated with an aOR of 1.07 (95% CI, 0.67–0.70).…”
Section: Discussionmentioning
confidence: 99%